Front–Rear Polarization by Mechanical Cues: From Single Cells to Tissues. Issue 6 (June 2016) - Ladoux, Benoit; Mège, René-Marc; Trepat, Xavier
Abstract : Directed cell migration is a complex process that involves front–rear polarization, characterized by cell adhesion and cytoskeleton-based protrusion, retraction, and contraction of either a single cell or a cell collective. Single cell polarization depends on a variety of mechanochemical signals including external adhesive cues, substrate stiffness, and confinement. In cell ensembles, coordinated polarization of migrating tissues results not only from the application of traction forces on the extracellular matrix but also from the transmission of mechanical stress through intercellular junctions. We focus here on the impact of mechanical cues on the establishment and maintenance of front–rear polarization from single cell to collective cell behaviors through local or large-scale mechanisms. Trends: Physical properties of the environment have functional roles in cell polarization. Rigidity sensing is not only governed by local dynamics of focal adhesions but also by large-scale actin cytoskeleton polarization. Matrix stiffness regulates the internal rheological properties of the cytoskeleton. Single cell polarization depends on the coupling between actin and microtubule cytoskeletons. Polarization within multicellular assemblies is regulated by a crosstalk between cell–matrix and cell–cell adhesions. Large-scale coordinated movements within epithelial cell sheets depend on external physical constraints.